Vertical mobility around the high-alpine Schnidejoch Pass. Indications of Neolithic and Bronze Age pastoralism in the Swiss Alps from paleoecological and archaeological sources. (10th August 2018) - Hafner, Albert; Schwörer, Christoph
Abstract: Since 2003 a melting ice field on the Schnidejoch Pass (2756 m a.s.l.) has yielded several hundred objects from the Neolithic period, the Bronze and Iron Ages and from Roman and early medieval times. The oldest finds date from the beginning of the 5th millennium BC, whilst the most recent artefacts date from around AD 1000. Most of the objects belong to the Neolithic period and the Bronze Age and are of organic origin. A series of over 70 radiocarbon dates confirm that the Schnidejoch Pass, which linked the Bernese Oberland with the Rhône Valley, was frequented from no later than 4800–4500 BCE onwards. The pass was easily accessible when the glaciers descending from the nearby Wildhorn mountain range (summit at 3248 m a.s.l.) were in a retreating phase. On the other hand, the area was impassable during periods of glacial advances. A recent palaeoecological study of sediment cores from nearby Lake Iffigsee (2065 m a.s.l.) provides clear indications of early human impact in this Alpine area. Linking archaeological finds from the Schnidejoch Pass and the Rhône Valley with the palaeoecological data provides results that can be interpreted as early indications of Alpine pastoralism and transhumance. The combined archaeological and paleoecological research allows us to explain vertical mobility in the Swiss Alps.